Major histocompatibility complex recombinant R13 antibody response against bovine red blood cells1 - N.G. Wilkinson; R.T. Kopulos; L.M. Yates; W.E. Briles; R.L. Taylor, Jr. (Poultry Science, 2020)
Recombination within the chicken major histocompatibility complex (MHC) has enabled more precise identification of genes controlling immune responses. Chicken MHC genes include BF, MHC class I; BL, MHC class II; and BG, MHC class IV that are closely linked on chromosome 16. A new recombination occurred during the 10th backcross generation to develop congenic lines on the inbred Line UCD 003 (B17B17) background. Recombinant R13 (BF17-BG23) was found in a single male chick from the Line 003.R1 (BF24-BG23) backcross. An additional backcross of this male to Line UCD 003 females increased the number of R13 individuals. Two trials tested this new recombinant for antibody production against the T cell–dependent antigen, bovine red blood cells. Fifty-one progeny segregating for R13R13 (n = 10), R13B17 (n = 26), and B17B17 (n = 15) genotypes were produced by a single R13B17 male mated to 5 R13B17 dams. One milliliter of 2.5% bovine red blood cell was injected intravenously into all genotypes at 4 and 11 wk of age to stimulate primary and secondary immune responses, respectively. Blood samples were collected 7 d after injection. Serum total and mercaptoethanol-resistant antibodies against bovine red blood cell were measured by microtiter methods. The least squares ANOVA used to evaluate all antibody titers included trial and B genotype as main effects. Significant means were separated by Fisher's protected least significant difference at P < 0.05. R13R13 chickens had significantly lower primary total and mercaptoethanol-resistant antibodies than did the R13B17 and B17B17 genotypes. Secondary total and mercaptoethanol-resistant antibodies were significantly lower in R13R13 chickens than in R13B17 but not B17B17 chickens. Gene differences generated through recombination impacted the antibody response of R13 compared with B17. Secondary antibody titers were not substantially higher than the primary titers suggesting that the memory response had waned in the 7-wk interval between injections. Overall, the results suggest that the lower antibody response in R13R13 homozygotes may be caused by recombination affecting a region that contributes to higher antibody response.